Pendekatan Preventif : Edukasi dan Penapisan Asam Urat pada Populasi Lanjut Usia di Panti Werdha Hana - Gunawan, Shirly; Santoso, Alexander Halim; Averina, Frilliesa; Sugiarto, Hans (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Hyperuricemia is a medical condition characterized by an increase in uric acid levels in the blood above normal limits, which is more than 7 mg/dL in men and more than 6 mg/dL in women. This condition is often found in the elderly due to decreased kidney function that occurs with the aging process. Hyperuricemia can increase the risk of gouty arthritis, kidney disorders, and cardiometabolic diseases such as hypertension and dyslipidemia. Community Service Activities (PKM) at Panti Werdha Hana aim to increase awareness among the elderly about the importance of early detection of uric acid levels and education on their prevention and management. This activity utilizies the Plan-Do-Check-Act (PDCA) method, where uric acid levels are measured, and educational materials are provided on uric acid and its associated risk factors. Participants with have uric acid levels above the normal threshold are provided with additional education and recommendations for medical follow-up. The results showed that of the 76 elderly who participated in the activity, 12 people (15.79%) experienced hyperuricemia, while 64 people (84.21%) had uric acid levels within the normal range. Early detection of uric acid levels is a crucial step in preventive efforts against more serious complications, as well as a key basis for planning sustainable health interventions to enhance the quality of life for the elderly.